Vibration Energy Harvesting for Wireless Sensors - Hadas, Zdenek; Zelenika, Saša; Pakrashi, Vikram (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Kinetic energy harvesters are a viable means of supplying low-power autonomous electronic systems for the remote sensing of operations. In this Special Issue, through twelve diverse contributions, some of the contemporary challenges, solutions and insights around the outlined issues are captured describing a variety of energy harvesting sources, as well as the need to create numerical and experimental evidence based around them. The breadth and interdisciplinarity of the sector are clearly observed, providing the basis for the development of new sensors, methods of measurement, and importantly, for their potential applications in a wide range of technical sectors.